Pendekatan Pembelajaran dengan Memperhatikan Cara Kerja Otak: Efektivitas Hypnotheaching dalam Mendongkrak Prestasi Belajar Siswa MAN 1 Model Bojonegoro - Anita Wijayanti (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2017)
Hypnoteaching is one of the teaching methods that concerns the existence of the brain as a source of thinking for students. This approach applies to process the brain waves of students to be in alpha conditions, because in this condition students can to suggest themselves of the importance of learning. This method of learning presents the subject matter by using subconscious languages ??because the subconscious is dominating the way the brain works. Any teacher clever if not able to process the sense of students then the learning will take place without the impression that ultimately has no significance to achievement. This paper presents the steps of hypnoteaching for teachers to be easily adopted in the process of teaching and learning activities. The result data showed that students' learning achievement and absorption capacity of 88% and 92% of XII MIPA and XI MIPA MAN 1 Model Bojonegoro axles respectively, and showed a high and medium deviation standard with the spread of homogeneous values ??and has a range of values ??that are not too far between the highest value and the lowest value.